Implementation of the jucama learning model assisted by tangram media to improve students’ mathematical creative thinking skills in plane figure material - Lutfia, Annizatul Lizza Mei; Fathani, Abdul Halim; Alifiani, Alifiani (International Journal of Trends in Mathematics Education Research, 2023)
The mathematical creative thinking skill is crucial in learning mathematics. However, the problem encountered in learning mathematics in class VII-B at SMP (Junior High School) Wahid Hasyim Malang was that the teacher did not involve students in exploring and providing opportunities to improve mathematical creative thinking skills. In overcoming this problem, the researcher applied the Jucama learning model assisted by tangram media on plane figure material. This research design was Classroom Action Research (CAR) which consisted of (1) Planning, (2) Implementation, (3) Observation, and (4) Reflection. The research subjects were 30 students in class VII-B SMP Wahid Hasyim. Data was collected through teacher and student activity observations, end-of-cycle test results, and questionnaires. This research was conducted in two cycles, with two meetings. The results indicated an increase in the percentage of observations of teacher and student activities, end-of-cycle test results, and questionnaire results. The results of observations of teacher activities in cycle I reached an average percentage of 75%, while in cycle II, it increased to 86.875%. The results of observing student activities in the first cycle reached a percentage of 73.125%, while in the second cycle, it increased to 85.75%. The end-of-cycle I test results showed that the completeness of student learning outcomes attained 63.33% with an average class score of 72. In comparison, the completeness of student learning outcomes in cycle II increased to 86.67%, with an average class score of 83.47. The results of the questionnaire in cycle I indicated that the percentage of success reached 46.67%, while in cycle II, the questionnaire results increased, with the percentage of success attaining 83.33%. Based on the results of data analysis, it can be implied that applying the JUCAMA learning model assisted by tangram media could improve the mathematical creative thinking skill of class VII-B students of SMP Wahid Hasyim Malang in the plane figure material.